(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Plant species of family Poaceae have important roles in rural economic and daily human life. They have been used in constructional building, tools, handicrafts, pulps, vegetables, fodder, baskets, traditional medicine, etc. Inventory to know the plant species and potentials of Poaceae were conducted in the Purwodadi Botanic Garden through observation in fields, interview, and literature studies. The results showed that there were 25 species of bamboos and 36 species of grasses in the garden. The bamboos genera Bambusa and Gigantochloa have more species than the other genera. Polytrias amaura, Axonopus compressus, and Oplismenus burmanni were the common and dominant grasses in the garden. Â© 2004 Jurusan Biologi FMIPA UNS Surakarta Key words: bamboos, grasses, Poaceae, Purwodadi Botanic Garden